Penerapan Problem Based Learning Berbantuan Media Augmented Reality untuk Meningkatkan Hasil dan Kemandirian Belajar - I Wayan Ekayogi (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
This research aims to improve learning outcomes and student learning independence by applying a problem-based learning model assisted by augmented reality media in III grade students at SD Negeri 5 Sebatu. This research is a classroom research action conducted in two cycles. The research subjects were III grade students, the total number of the students were 24 students. The object of the research is a problem-based learning model assisted by augmented reality media, learning outcomes and learning independence. The data in the research were collected by test and observation methods. Data were analyzed using descriptive statistical and quantitative descriptive analysis methods. Based on the results of data analysis, the average percentage of students cognitive learning outcomes in cycle I was 67.08% (moderate category), increasing to 81.25% (high category) in cycle II. The results of observations of learning independence cycle I meeting 1were in the